Water on Mars and life - Tokano, Tetsuya (Advances in astrobiology and biogeophysics, 2005)
Water on Mars and Life" surveys recent advances made in research into water on Mars together with its astrobiological implications. This volume addresses not only scientists working in the field but also nonspecialists and students in search of a high-level but accessible introduction to this field of research